CXCL5 Downregulation in Villous Tissue Is Correlated With Recurrent Spontaneous Abortion - Zhang, Sainan; Ding, Jinli; Wang, Jiayu; Yin, Tailang; Zhang, Yan; Yang, Jing (Frontiers in Immunology, 2021)
Recurrent spontaneous abortion (RSA) affects 5% of childbearing age women worldwide. Inadequate trophoblast invasion is one of the main reasons for the development of RSA, however, the underlying molecular mechanisms for RSA have not been fully understood and further explanation is urgently needed. C-X-C motif chemokine ligand -5 (CXCL5) is reported to contribute to the invasion of cancer cells and its aberrant expression is associated with the cellular process of tumor pathology. Considering the high behavioral similarity between trophoblast cells and cancer cells, we hypothesized that CXCL5 may influence trophoblast invasion, and its expression levels in villous tissue may be correlated with RSA. In this study, we firstly investigated the CXCL5 expression in placental villous tissues of 15 RSA patients and 13 control patients, and the results showed that CXCL5 levels were significantly lower in villous tissue from RSA patients than that of the controls. Further in vitro experiments presented that recombinant human CXCL5 can enhance trophoblast migration, invasion, and epithelial-to-mesenchymal transition (EMT) process. We also demonstrated that CXCL5 exerted these effects on trophoblast cells through PI3K/AKT/ERK1/2 signaling pathway. In conclusion, these data indicate that CXCL5 down-regulation in human villous tissue is correlated with RSA. Additionally, we found that estrogen, progesterone, human chorionic gonadotropin, as well as decidual stromal cells can regulate CXCL5 and CXCR2 expression of trophoblast in a cell manner.